Trends in the development of legislation on liability for robbery (Journal of actual problems of jurisprudence, 2018)
The article considers the main stages of development of criminal law on liability for robbery, analyzed its current status. Particular attention is paid to the analysis of legal regulation of robbery in the history of the criminal legislation of Kazakhstan, as legal scholars pay attention to the participation of this dangerous manifestations of crime in our country. Robbery is one of the most dangerous and the most common crimes. In this regard, problems of increasing the efficiency of the fight against looting through the application of criminal law getting particular relevance to science and criminal law enforcement activities.Key words: property, thievery, robbery, stealing, theft, violence, attack, brigandage.